2018
DOI: 10.1002/ece3.4078
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) and its parasitoids on vegetables and cassava plants in Burkina Faso (West Africa)

Abstract: The whitefly Bemisia tabaci is a pest of many agricultural and ornamental crops worldwide and particularly in Africa. It is a complex of cryptic species, which is extremely polyphagous with hundreds of host plants identified around the world. Previous surveys in western Africa indicated the presence of two biotypes of the invasive MED species (MED‐Q1 and MED‐Q3) living in sympatry with the African species SSA and ASL. This situation constitutes one of the rare cases of local coexistence of various genetic enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…MED is a globally important B. tabaci haplotype group which is thought to have originated from Africa. Consequently, there are numerous other reports of its prevalence on a wide range of crop and weed hosts [59,60,64]. B. tabaci MED has been reported to be extremely polyphagous and invasive [54], causing damage to both field and greenhouse crops [82].…”
Section: Resultsmentioning
confidence: 99%
“…MED is a globally important B. tabaci haplotype group which is thought to have originated from Africa. Consequently, there are numerous other reports of its prevalence on a wide range of crop and weed hosts [59,60,64]. B. tabaci MED has been reported to be extremely polyphagous and invasive [54], causing damage to both field and greenhouse crops [82].…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, our results indicate that lantana is a particularly challenging host for B. tabaci complex members. This could explain why, in the field, populations reported on this plant are restricted to MED ( 39 , 41 , 58 ), including in areas where other B. tabaci species co-occur, such as the close relative polyphagous MEAM1 (Middle East Asia minor 1) species ( 59 ). It is tempting to associate this impairment with the lowest nutritional quality of lantana, which contains the smallest amount of the four EAAs, Ile, Leu, Phe, and Val, among the three plants considered in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research demonstrated that aphid performance is associated with the aminoacid composition of the phloem sap (44)(45). It could explain why Hemipteriphilus was not present in the SSA species which, contrary to MED and ASL which have been found in several host plant species, has only been detected on cassava in Burkina Faso (34). Analysis of the genome of Hemipteriphilus, with a special focus on genes involved in metabolic pathways, would give further insight into its putative nutritional role.…”
Section: Discussionmentioning
confidence: 99%
“…In this country, B. tabaci is a pest of primary importance, with a severe impact on economic activity (28). Indeed, B. tabaci is a cryptic species complex (42 species reported till now based on a 657bp portion of the mitochondrial cytochrome oxidase 1 ( mtCOI ) DNA sequence: 2933), and in Burkina Faso individuals belong either to SSA (Sub-Saharan Africa), ASL (Africa Silver-Leafing) or MED (Meditteranean) species (34). Using universal bacterial primer sets we detected few bacterial species and, more importantly, no new putative S-symbiont.…”
Section: Introductionmentioning
confidence: 99%